Research on shredding process and characteristics of multi-material plates for recycled cars. (October 2016) - Zhou, Xianyan; Hu, Zhili; Xiao, Xiang; Li, Mingbo
To cope with the problems of energy shortage and environmental pollution caused by the large number of retired cars, the energy efficiency of shredding recycled car bodies urgently needs to be improved. Before shredding, recycled car bodies are always cut into shaped metal plates and piled in several sheets like sandwich plates. Currently, the lightweight design philosophy has driven the widespread application of multi-materials in car bodies. In this study, the finite element and experimental methods are used to analyse the shredding process of multi-material plates from recycled car bodies in order to determine the characteristics of plates with different thicknesses and materials. The results showed that the shredding efficiency of steel laminates with less than three sheets is quite low although the efficiency can be raised by increasing the thickness. The shredding energy efficiency is higher for Al alloy laminates than for steels. The shredding energy efficiency can be improved by raising the strength of the shredding material. The results of this study proved that the shredding energy consumption can be reduced by shredding the different materials of the multi-material boards separately.